2018
DOI: 10.3889/oamjms.2018.264
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Allergic Rhinitis: It’s Effect on the Immune System and Clinical Symptoms

Abstract: BACKGROUND:Allergic rhinitis is one of the most common allergic diseases and characterised by sneezing, rhinorrhea, nasal congestion and nasopharyngeal itching. Subcutaneous immunotherapy (SCIT) for specific allergens is an effective treatment and induces the inhibitory effect of T regulatory lymphocytes and decreases clinical symptoms in allergic rhinitis.AIM:In this study effect of subcutaneous immunotherapy with specific allergens on clinical symptoms and T regulatory and T Helper cells cytokines, in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Various immune-related factors are involved in its development and progression, including chemokines and their receptors, EPO, interleukin and its receptors, and leukotrienes. 3 The vitamin D receptor (VDR) gene can regulate immune responses in the body, inhibit abnormal cell activation, and maintain the stability of cell function. 4 A number of clinical studies have confirmed that vitamin D can effectively prevent and treat bronchial asthma by regulating the immune system, and both AR and bronchial asthma have similar etiology and pathogenesis and belong to the same category of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Various immune-related factors are involved in its development and progression, including chemokines and their receptors, EPO, interleukin and its receptors, and leukotrienes. 3 The vitamin D receptor (VDR) gene can regulate immune responses in the body, inhibit abnormal cell activation, and maintain the stability of cell function. 4 A number of clinical studies have confirmed that vitamin D can effectively prevent and treat bronchial asthma by regulating the immune system, and both AR and bronchial asthma have similar etiology and pathogenesis and belong to the same category of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical treatment of AR mainly includes avoiding contact with allergens, drug treatment, and immunotherapy. However, studies on effective drugs in prevention and treatment of AR progress slowly, and immunotherapy still remains the most effective treatment in clinical practice [5]. Thus, it is urgent to develop novel approaches to the treatment of AR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in further studies, it might be possible to show that Th polarization modulation can be exploited to treat DM and AR. In fact, immunotherapy based on Th polarization is already being executed for AR treatment 19 . In the same manner, application of Th polarization in DM treatment could also be possible.…”
Section: Discussionmentioning
confidence: 99%